2019
DOI: 10.1176/appi.ajp.2018.18040429
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar-Prefrontal Network Connectivity and Negative Symptoms in Schizophrenia

Abstract: The interpretability of results in psychiatric neuroimaging is significantly limited by an overreliance on correlational relationships. Purely correlational studies cannot alone determine whether behavior-imaging relationships are causal to illness, functionally compensatory processes, or purely epiphenomena. Negative symptoms (e.g., anhedonia, amotivation, and expressive deficits) are refractory to current medications and are among the foremost causes of disability in schizophrenia. The authors used a two-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
194
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(228 citation statements)
references
References 44 publications
(42 reference statements)
17
194
0
Order By: Relevance
“…These findings are consistent with the observations that there are distinct and topographically precise CB contributions to cerebral intrinsic connectivity networks [24,25,39] and that rTMS applied to distinct CB regions can selectively modulate network functional connectivity in healthy individuals [145,216]. Further, dysfunctional connectivity between the CB and the dorsolateral prefrontal cortex is associated with negative symptom severity in schizophrenia, and improvement of the connectivity ameliorates the severity of the negative symptoms [217].…”
Section: Ccas In the Hereditary Ataxiassupporting
confidence: 88%
“…These findings are consistent with the observations that there are distinct and topographically precise CB contributions to cerebral intrinsic connectivity networks [24,25,39] and that rTMS applied to distinct CB regions can selectively modulate network functional connectivity in healthy individuals [145,216]. Further, dysfunctional connectivity between the CB and the dorsolateral prefrontal cortex is associated with negative symptom severity in schizophrenia, and improvement of the connectivity ameliorates the severity of the negative symptoms [217].…”
Section: Ccas In the Hereditary Ataxiassupporting
confidence: 88%
“…Compensatory reorganization changes are generally expected to correlate with improved behavioral function; although not necessarily, since it would also be reasonable to expect that compensatory mechanisms become more prominent as disease severity, and thus behavioral abnormalities, become more pronounced. Studies of neural stimulation might be able to provide causal evidence of cerebellar compensation in brain disorders, and indeed, recent studies in neuropsychiatry report behavioral improvement after cerebellar stimulation [129,130]. Technological advancements that allow targeting small and deep brain structures [131][132][133][134][135] underscore the potential for cerebellar stimulation to become a useful therapeutic modality in the clinical treatment of cognitive dysfunction.…”
Section: Cerebellar Cognitive Reserve (Guell X Schmahmann Jd)mentioning
confidence: 99%
“…In the specific case of cerebellar cortex, damage to the cerebellar posterior lobe, which provides inputs to the DN, causes the cerebellar cognitive affective syndrome, characterized by deficits in executive, linguistic, visuospatial and affective processing (Guell et al 2015;Hoche et al 2016Hoche et al , 2018Schmahmann & Sherman 1998, Schmahmann et al 2009, Stoodley et al 2016). In addition, multiple studies have reported cerebellar cortical abnormalities in numerous disorders such as Alzheimer's disease (Guo et al 2016, Jacobs et al 2018, autism spectrum disorder (Arnold Anteraper et al 2018, D'Mello & Stoodley 2015, and schizophrenia (Moberget et al 2018), with preliminary evidence suggesting that cerebellar cortical stimulation might improve symptoms in these diseases (Brady et al 2019, Demirtas-Tatlidede et al 2010, Di Lorenzo et al 2013, Garg et al 2016, Stoodley et al 2017, Tikka et al 2015. The importance of our findings is thus underscored by the relevance of cerebellar cortex in neurology and psychiatry (Schmahmann et al 2019), as the majority of fibers exiting the cerebellar cortex synapse in DN before reaching extracerebellar structures such as cerebral cortex.…”
Section: Relevance For Cerebellar Neuroscience Neurology and Psychimentioning
confidence: 99%